إدارة الجودة في تعليم اللغة العربية بمدرسة أولى الألباب نهضة الوطن الثانوية الإسلامية لندنج جارن لومبوك الشرقية - Hamzani Hamzani (LUGATUNA ¦ Jurnal Prodi PBA, 2018)
Quality management is system management based the quality of to reach the standard established and meet the needs of customers, Islamic High School Ulil Albab NW Lendang Jaran East Lombok is having mission to improve the ability students in english and arabic language. Arabic Learning supported with extracurricular program and speaking environment . In the school , students are obliged to use arabic for a whole week and english language alternately. In this research the researchers found: 1) quality management planning of Arabic learning adopted by taking into account: the first standard arabic learning (planning standard, standards in implementing and standards evaluation) that are set up madrasah managers, second, standard planning from the government; 2) quality management implementation of arabic learning do by using the method, media varying supported with extracurricular programs as speech arabic, arabic camp, PAS (devotion the end of the students) and speaking environment; 3) quality management evaluation of arabic learning use: test (oral or written), non test (observation and questionnaire). Key Word: Quality Management, Arabic Learning